Refis: uma análise das empresas brasileiras de capital aberto aderentes do Pert 2017 - Severiano, Débora Araújo (2020)
This study aimed to address, in the light of the theories of Social Responsibility, Organizational Ethics and Corporate Reputation, socially unfair organizational practices. Through the study of the adherence of Brazilian publicly traded companies to the Special Tax Regularization Program (PERT) offered by the Government in 2017, we sought to identify the reasons that lead companies to opt for the installment payment of unpaid taxes. For this, the indicators of dividends paid (payout), Net debt/EBITDA, EBITDA, margin and general indebtedness for the years 2015 to 2018 were analyzed, with the objective of detecting significant differences between the financial framework of companies that joined the program from those that did not. joined. Quantitative in nature, the study looked for significant differences between means with the use of the Student t test, comparing the indicators of the companies that adhered to the installment plan with those that did not. The results suggested that, although the program was targeted at companies in adverse situations, many others ended up benefiting from these measures in an abusive way, using them as a cheaper form of financing, increasing their competitiveness unfairly, not fulfilling their social role and also, becoming recurrent defaulters, negatively affecting the tax collection in the country, and consequently, the well-being of society.